A multielement isotopic study of refractory FUN and F CAIs: Mass-dependent and mass-independent isotope effects. (15th January 2018) - Kööp, Levke; Nakashima, Daisuke; Heck, Philipp R.; Kita, Noriko T.; Tenner, Travis J.; Krot, Alexander N.; Nagashima, Kazuhide; Park, Changkun; Davis, Andrew M.
Abstract: Calcium-aluminum-rich inclusions (CAIs) are the oldest dated objects that formed inside the Solar System. Among these are rare, enigmatic objects with large mass-dependent fractionation effects (F CAIs), which sometimes also have large nucleosynthetic anomalies and a low initial abundance of the short-lived radionuclide 26 Al (FUN CAIs). We have studied seven refractory hibonite-rich CAIs and one grossite-rich CAI from the Murchison (CM2) meteorite for their oxygen, calcium, and titanium isotopic compositions. The 26 Al- 26 Mg system was also studied in seven of these CAIs. We found mass-dependent heavy isotope enrichment in all measured elements, but never simultaneously in the same CAI. The data are hard to reconcile with a single-stage melt evaporation origin and may require reintroduction or reequilibration for magnesium, oxygen and titanium after evaporation for some of the studied CAIs. The initial 26 Al/ 27 Al ratios inferred from model isochrons span a range from <1 × 10 −6 to canonical (∼5 × 10 −5 ). The CAIs show a mutual exclusivity relationship between inferred incorporation of live 26 Al and the presence of resolvable anomalies in 48 Ca and 50 Ti. Furthermore, a relationship exists between 26 Al incorporation and Δ 17 O in the hibonite-rich CAIs (i.e., 26 Al-free CAIs have resolved variations in Δ 17 O, while CAIs with resolved 26 Mg excesses have Δ 17 O values close to −23‰). Only the grossite-rich CAI has a relatively enhanced Δ 17 O value (∼−17‰) in spite of a near-canonical 26 Al/ 27 Al. We interpret these data as indicating that fractionated hibonite-rich CAIs formed over an extended time period and sampled multiple stages in the isotopic evolution of the solar nebula, including: (1) an 26 Al-poor nebula with large positive and negative anomalies in 48 Ca and 50 Ti and variable Δ 17 O; (2) a stage of 26 Al-admixture, during which anomalies in 48 Ca and 50 Ti had been largely diluted and a Δ 17 O value of ∼−23‰ had been achieved in the CAI formation region; and (3) a nebula with an approximately canonical level of 26 Al and a Δ 17 O value of ∼−23‰ in the CAI formation region.